Do florilégio à antologia da Poesia Brasileira da invenção: uma reflexão sobre o paradigma da história da Literatura Brasileira - Cairo, Luiz Roberto Velloso (Aletria: Revista de Estudos de Literatura, 1995)
This paper aims to discuss the Brazilian Literary History model, a polemic issue, which concerned the romantic and realistic Brazilian criticism and still arouses the interest of contemporary criticism.